Numerical Solution of Rare Metal Leaching Problem - Galtsev, Oleg V.; Galtseva, Oksana A.; Belenko, Vladimir A.; Mamatov, Alexander V.; Nemtsev, Alexander N.; Mishunin, Vadim V. (International Journal of Engineering and Technology, 2018)
Â It is well known that a lot of chemical and physical processes take place on the surfaces of interaction between solid and liquid substances. These processes include a very important technological process of uranium, nickel, copper, precious metal and other solid compound extraction - in-situ leaching. In this article we will rely on the mathematical description of these complex systems proposed by A.M. Meirmanov, where the main idea is the presence of new conditions on a free (unknown) boundary between liquid and solid phases (â€œpore space - solid skeletonâ€). These conditions express the usual laws of mass conservation of mass and the development of the mathematical model describing the processes at the macroscopic level. The method proposed in the book allows us to study numerically the dependence ways of free boundary dynamics on a heterogeneous solution distribution velocity and external parameters (reagent temperature, pressure and concentration).